2020
DOI: 10.1038/s41598-020-69756-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum isolate with histidine-rich protein 2 gene deletion from Nyala City, Western Sudan

Abstract: In remote areas of malaria-endemic countries, rapid diagnostic tests (RDTs) have dramatically improved parasitological confirmation of suspected malaria cases, especially when skilled microscopists are not available. This study was designed to determine the frequency of Plasmodium falciparum isolates with histidine-rich protein 2 ( pfhrp2 ) gene deletion as one of the possible factors contributing to the failure of PfHRP2-based RDTs in detecting malaria. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…For the present study, a multiplex qPCR assay — recently validated as a one-step genotyping method ( Grignard et al, 2020 ) — was used to demonstrate that false-negative RDT results were caused by the deletion of pfhrp2 / 3 in three patients. Our results confirmed that pfhrp2 / 3 -deleted parasites are in circulation in Ethiopia and Sudan, as previously reported ( Boush et al, 2020 , Girma et al, 2019 , Golassa et al, 2020 , Mussa et al, 2019 ). Interestingly, a mathematical modelling exercise ( Watson et al, 2017 ) predicted the insurgence of such parasites in African countries with low endemicity, such as Sudan, Somalia, or Ethiopia, which were the travel origins of the patients we analysed.…”
Section: Discussionsupporting
confidence: 93%
“…For the present study, a multiplex qPCR assay — recently validated as a one-step genotyping method ( Grignard et al, 2020 ) — was used to demonstrate that false-negative RDT results were caused by the deletion of pfhrp2 / 3 in three patients. Our results confirmed that pfhrp2 / 3 -deleted parasites are in circulation in Ethiopia and Sudan, as previously reported ( Boush et al, 2020 , Girma et al, 2019 , Golassa et al, 2020 , Mussa et al, 2019 ). Interestingly, a mathematical modelling exercise ( Watson et al, 2017 ) predicted the insurgence of such parasites in African countries with low endemicity, such as Sudan, Somalia, or Ethiopia, which were the travel origins of the patients we analysed.…”
Section: Discussionsupporting
confidence: 93%
“…Eritrea's alarming reports of false-negative RDTs due to pfhrp2/3-deleted parasites prompted an immediate change in national diagnostic testing policy in 2016 14,38 . Recent evidence from Sudan, Djibouti and Somalia suggests that the Horn of Africa may already be heavily affected by pfhrp2/3-deleted parasites 39,40 , although results from ongoing surveillance efforts are not yet publicly available. Within affected regions in Ethiopia, we observed spatial heterogeneity in P. falciparum RDT profiles by district, with prevalence of the discordant HRP2−, Pf-LDH+ RDT profile ranging from 1 to 30% (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Eritrea’s alarming reports of false-negative RDTs due to pfhrp2/3- deleted parasites prompted an immediate change in national diagnostic testing policy in 2016 15,36 . Recent evidence from Sudan, Djbouti, and Somalia suggests that the Horn of Africa may already be heavily affected by pfhrp2/3- deleted parasites 37,38 , though results from ongoing surveillance efforts are not yet publicly available. Within affected regions in Ethiopia, we observed spatial heterogeneity in P. falciparum RDT profiles by district, with prevalence of the discordant HRP2-, PfLDH+ RDT profile ranging from 0.9 to 30% ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%